Dynamic stability improvement of a large-scale machine power system with a DFIG-based wind farm using a generalized unified power-flow controller (GUPFC) - Nguyen Thi Mi Sa (Journal of Technical Education Science, 2017)
This research proposes the dynamic stability improvement of a large-scale power system which consists of a conventional synchronous generator (SG)-based power plant integrated with a doubly-fed induction generator (DFIG)-based wind farm by using a generalized unified power-flow controller (GUPFC). The complete dynamic mathematical equations of the studied system are established in dq-axis reference frame under three-phase balanced conditions. In addition to the power flow control function of the GUPFC, a proportional-integral-derivative (PID) type oscillation damping controller (ODC) is designed for the GUPFC to offer adequate damping for the studied system. The proposed ODC for the GUPFC is designed using the pole assignment method based on modal control theory. The steady-state analysis and time-domain simulation results show that the studied system without GUPFC suffers from low-damped low-frequency oscillations due to the electromechanical mode of the SGs. The damping of these oscillations, however, is slightly increased when the GUPFC is implemented in the transmission line for controlling the power flow. The results obtained also show that the designed ODC for the GUPFC can significantly increase the damping and, hence, effectively improve the dynamic stability of the studied system under various disturbance conditions.